INTERNAL REGIONAL FACTORS INFLUENCING GEOPOLITICAL PROCESSES IN CENTRAL ASIA - Sadieva Guzal Olimovna (Sciental Journals Publishing, 2025)
This article analyzes the mechanisms for strengthening mutual trust and the development of new political approaches in the Central Asian region. It explores the importance of regional cooperation in ensuring political stability, economic integration, and security. Particular attention is given to the “Central Asia-2040” Concept adopted by the leaders of Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, which aims to institutionalize multilateral cooperation and enhance dialogue among regional states. The study highlights the necessity of expanding economic ties, ensuring interethnic harmony, and deepening cooperation in education, culture, and information spheres as key factors for sustainable regional development. The paper concludes that building mutual trust, strengthening integration processes, and effectively using international mechanisms are vital for achieving stability and prosperity in Central Asia.
Keywords: Central Asia, regional cooperation, mutual trust, political dialogue, integration, security, Central Asia-2040 Concept, interethnic harmony, economic partnership, stability.